REVIEW OF THE FEASIBILITY OF PIONEERING SHIP SUBSIDIES ON KMP. PULO TELLO ON THE BENGKULU-ENGGANO TRAFFIC, BENGKULU PROVINCE - Diani, Oktrianti; Sari, Vita Permata; Latuheru, Paulina M; Dewi, Dahlia Apriani; Wahyuni, Destiana (IWTJ : International Water Transport Journal, 2024)
In Bengkulu Province there is a ferry port that serves 1 (one) route, namely the Bengkulu-Enggano route with a distance of 106 km. This port has been operating since 2018, in the operation of the ferry, the Ship Operational Cost (BOK) is still subsidized by the central government. To review the provision of subsidies that are still provided by the government on the Bengkulu-Enggano Route, this is done to review the pioneering status on the route whether it is still feasible or not to be provided by the government, and as an evaluation material so that the management of the Bengkulu-Enggano Route crossing transportation can continue to develop and more than that as a comparison that can allow this route to be free from government subsidies and become a commercial route and to reduce the financial burden and subsidies from the government. In this study, the researcher used a quantitative method by calculating the Ship Operating Cost (BOK), ship income, and Break Event Point (BEP). From the results of the analysis, it can be concluded that the ship's load factor in 2023 is 43%, the ship's operational cost per year is IDR 15,081,840,683. It can be concluded that the operation of the crossing ship is still experiencing losses, so the ship still has to get subsidies from the central government to support the operation of the ship. Based on the results of the crossing transportation forecast in 2032, the ship's load factor has reached the Break Event Point (BEP) of 92% with ship operational costs of IDR. 20,555,000,749 so that in 2032 it can be recommended to be a commercial route.